Wall mural of goddess Ganga - Banganga by Ghosh, Ayan (2023)
In Hinduism, the River Ganges is worshipped as a fertility goddess, the giver of life and the protector of humanity. This wall mural of the goddess Ganga, the personification of the river Ganges, was painted by artist Shilo Shiv Suleman on a wall face at Walkeshwar. It is believed the water of Banganga Tank is as pure as the water of the River Ganges, the holiest of all rivers, hence it is used for purification purposes during Hindu rituals and ashes are immersed in it.